Critical data leak analysis in educational environment - Abdul Ghani Azmi, Ida Madieha; Ashraf, Qazi Mamoon; Zulhuda, Sonny; Daud, Mahyuddin (IEEE, 2016)
The rapid growth of computer technologies has resulted in a corresponding increase in the creation of new loopholes in systems which eventually might result in data leak. Data leakage is an incident in which sensitive information is released to any unauthorized party intentionally or unintentionally. There is a large set of software available which can be used to prevent data leak, however they fail to cover all the channels of leakage involved. Many institutions specifically educational institutions are in possession of large amounts of personal data. Due to the sheer size of these institutions, securing each and every system is overlooked. Educational institutions need to implement higher levels of security practices in their systems to stop any attempts of users trying to access critical data intentionally. If adequate measures are not taken, records belonging to the staff as well as students can be manipulated and used. We conduct a case study, and show the potential weaknesses and vulnerabilities that can exist in an educational environment which can be a path for data leak. The results have important implications on preventive measures that can be used by such institutions to avert data leak.